Pengendalian Persediaan Obat Di Pt. Pratapa Nirmala Palembang dengan Metode Heuristik Silver Meal (HSM) - Yuni Kartika; Evi Yuliza Yuliza; Fitri Maya Puspita (Jurnal Penelitian Sains, 2019)
Drug demand data is a top priority for a company in the process of ordering. In meeting consumer needs a plan is needed in the process of ordering drugs so that there is no vacancy and also the distribution process does not stop. This study  determine the results of drug inventory control orders and find out the total cost of ordering optimal drugs by applying the Heuristic Silver Meal (HSM) method. The total cost of ordering a drug before applying the HSM method is Rp. 29,016,000, while after applying the HSM method it produces a total booking fee of Rp. 20,800,632. Thus the results of the calculation of the method HSM are known to produce optimal ordering costs. This means that the company saves on ordering costs of Rp. 8,215,368, so the HSM method can be used to calculate the cost of ordering drugs at PT. Pratapa Nirmala Palembang.